Thrifting sebagai Ruang Publik Modern di Kalangan Remaja Indonesia: Sebuah Tinjauan Literatur Sistematis - Zahratul Hubbah; Shasrini, Tessa; Restia, Novi Dini (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2026)
This study aims to analyze the phenomenon of thrifting as a modern public sphere among Indonesian adolescents by examining its relationship with social media, consumer behavior, and sustainable consumption. The method used is a Systematic Literature Review (SLR) by analyzing relevant studies published within the last ten years. The findings indicate that thrifting has transformed from an alternative consumption activity into a modern lifestyle influenced by digital technological developments. Social media plays a significant role in shaping adolescents’ perceptions of second-hand clothing, shifting its image from being associated with poverty to becoming a trendy and sustainable lifestyle choice. Furthermore, thrifting functions as a digital public sphere that enables social interaction, information exchange, and identity formation among adolescents. However, the study also identifies the presence of an attitude–behaviour gap, referring to the discrepancy between environmental awareness and actual consumption behavior, where Generation Z still tends to engage in impulsive buying due to the influence of visual culture and social media. In this context, thrifting can be understood as a form of negotiation between sustainability values and modern consumption practices. This study concludes that thrifting is a multidimensional phenomenon reflecting the dynamics of consumption, communication, and sustainability in the digital era, and it holds potential as an alternative approach to promoting a more environmentally sustainable lifestyle.